PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP PROFITABILITAS UKM DENGAN ORIENTASI PASAR SEBAGAI VARIABEL PEMEDIASI - Maria Pampa Kumalaningrum (Jurnal Riset Manajemen dan Bisnis, 2011)
This study examined the effect of entrepreneurial orientation on profitability in small business mediated by market orientation. Entrepreneurial orientation reflects the degree to which firms’ growth objectives are driven bythe identification and exploitation of untapped market opportunities. Market orientation reflects the degree to which firms’ strategic market planning is driven by customer and competitor intelligence.Data was processed with Structural Equation Modeling using AMOS  program. The results showed that Entre-preneurial orientation has an direct effect onmarket orientation and indirect effect on profitability mediated by market orientation. The results suggest, at least in small firms, entrepreneurial orientation complements market orientation by instilling an opportunistic culture that impacts the firm’s profitability.Keywords:market orientation, entrepreneurial orientation, and profitability.